Budaya Keselamatan di Bengkel Perawatan Pesawat Udara pada Garuda Maintenance Facility (GMF AEROASIA) - Minda Mora (WARTA ARDHIA, 2011)
Safety is the most important thing in aviation. Safety level has to improved in highest performance. One way to improve safety is to implement safety culture in organization. In case of aviation safety, safety is affected by many factors. Aircraft maintenance is of the factor. The goal of his research is to asess the aviation safety culture in maintenance facilities, case study: Garuda Maintenance Facilities (GMF) using Safety Culture Indicator Scale Measurement System (SCISMS). The Safety Culture Grid System is used to analize the data. Result shows that safety culture in Garuda Maintenance Facilities is COLLABORATIVE. In a Collaborative safety culture, safety is seen as a primary integrated concern throughout the organization.